Preoperative Anesthesia Education: A Critical Element in Comprehensive Patient Management - Hou, Tian (International Journal of Public Health and Medical Research, 2025)
Preoperative anesthesia education constitutes a fundamental component of perioperative care, significantly contributing to the protection of patient autonomy through informed consent, reduction of preoperative anxiety, and promotion of clinical safety. Despite its importance, current clinical methodologies are often disjointed and overly procedural, inadequately addressing patient-specific concerns. This article synthesizes evidence from the literature and clinical case analyses to identify patients’ primary informational needs, elucidates the essential function of preoperative anesthesia education in fostering humanistic care, optimizing patient safety, and strengthening the therapeutic alliance. It further outlines a standardized educational framework complemented by tailored approaches to meet individual patient requirements. The article concludes with actionable recommendations to overcome prevailing barriers, advocating for the integration of preoperative anesthesia education as a cornerstone of patient-centered, humanistic healthcare.